2023
DOI: 10.3390/plants12101987
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Phytochemical Composition and Untargeted Metabolomic Analysis of an Extract from Cnidoscolus aconitifolius (Mill.) I. I. Johnst and Porophyllum ruderale (Jacq.) Cass. and Biological Cytotoxic and Antiproliferative Activity In Vitro

Abstract: Cnidoscolus aconitifolius (CA) and Porophyllum ruderale (PR) are representative edible plants that are a traditional food source in Mexico. This research aimed to analyze the phytochemical composition and untargeted metabolomics analysis of CA and PR and evaluate their antiproliferative effect in vitro. The phytochemical composition (UPLC-DAD-QToF/MS-ESI) identified up to 38 polyphenols and selected organic acids that were clustered by the untargeted metabolomics in functional activities linked to indolizidine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Despite the predictable association between P. ruderale polyphenols and biological mechanisms, the results must be taken cautiously, as in vivo and in vitro validation must be carried out. Although there is no information about the scientific examination of P. ruderale biological activity, our research group previously showed that P. ruderale leaves can reduce the metabolic activity of human SW480 colorectal cancer cells through a cytotoxic effect attributable to its polyphenolic composition, particularly rutin, epigallocatechin gallate, caffeic acid, and gallic acid [23]. Other authors reported the anti-inflammatory potential of P. ruderale extracts and attributed most of the effects to chlorogenic acid, several flavonoids, and ellagitannins [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the predictable association between P. ruderale polyphenols and biological mechanisms, the results must be taken cautiously, as in vivo and in vitro validation must be carried out. Although there is no information about the scientific examination of P. ruderale biological activity, our research group previously showed that P. ruderale leaves can reduce the metabolic activity of human SW480 colorectal cancer cells through a cytotoxic effect attributable to its polyphenolic composition, particularly rutin, epigallocatechin gallate, caffeic acid, and gallic acid [23]. Other authors reported the anti-inflammatory potential of P. ruderale extracts and attributed most of the effects to chlorogenic acid, several flavonoids, and ellagitannins [18].…”
Section: Discussionmentioning
confidence: 99%
“…The leaves were identified by a specialist from the Jerzy Rzedowski Herbarium of the Universidad Autónoma de Queretaro and sampled using the recommended acronyms of Thiers [28] as QMEX157. Once they arrived at the laboratory (all samples were processed 4 h after collection to standardize the transportation time from the collection sites to the laboratory), the leaves were processed as previously indicated in Vargas-Madriz et al [23]. Briefly, a forced-air-drying process at 40 • C for 72 h was conducted in an oven (FX 1375, Shel-Lab, Elkin, NC, USA), followed by grinding in an electric mill, sieving (0.5 mm particle size), storage in airtight bags, and freezing (Last II, REVCO, Twinsburg, OH, USA) at −80 • C.…”
Section: Preparation Of Plant Extracts Identification and Quantificat...mentioning
confidence: 99%
“…Similarly, Mfotie Njoya et al [ 70 ] showed that Croton gratissimus leaf extract exhibited cytotoxic effects on various cancer lines (A549, Caco-2, HeLa, MCF-7) and inhibited cancer cell growth through induction of caspase-3 (casp-3)/caspase-7 (casp-7) activation, with the highest induction (1.83-fold change) obtained on HeLa cells. Vargas-Madriz et al [ 71 ] presented that Cnidoscolus aconitifolius and Porophyllum ruderale , rich in polyphenols, reduced the metabolic activity of human SW480 colon adenocarcinoma cells. In addition, both extracts increased the total number of apoptotic cells and arrested the cell cycle in the G0/G1 phases.…”
Section: The Euphorbiaceae Family Of Plantsmentioning
confidence: 99%
“…nuttaliiae (huauzontle), and Chenopodium berlandieri ssp. Berlandieri (quelite cenizo) [2,3]. The last of these, quelite cenizo, is one of the most widely consumed plants in Mexico, and it is used extensively in several typical dishes and preparations [4].…”
Section: Introductionmentioning
confidence: 99%